q-Analog of the gap equation for cuprates - Ghosh, Angsula; Pimentel, B. M. [UNESP] (Elsevier B.V., 2012)
The q-deformed algebraic method based on the extension of the number concept as proposed by Gauss [1] is used to obtain a q-analog to the gap equation for the cuprates using a tight-binding model. The conventional s-wave symmetry along with the d(x2-y2) wave order parameter are considered to understand the effect of q-fermionic theory which is a generalization or deformation of the usual Fermi theory. The dependence of the gap and/or the critical temperature on doping for various values of q is studied. Specific heat and the phase diagram are found to be explicitly dependent on the parameter and the wellknown hump-like behavior is detected for q > 1. Moreover, the position of the maximum in T-c in the phase diagram depends on the value of q and also on the value of the coupling. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Cuprates; q-Algebra; Tight-binding model